Lights on the shadows of public procurement: Transparency as an antidote to corruption. Issue 3 (13th August 2019) - Bauhr, Monika; Czibik, Ágnes; de Fine Licht, Jenny; Fazekas, Mihály
Abstract: The increased focus on marketizing mechanisms and contracting‐out operations following the New Public Management reform agenda has sparked a debate on whether the close interactions between public and private actors might drive corruption in the public sector. The main response to those worries has been increased transparency, but so far empirical evidence of its efficiency remains scant and mixed. This article argues that the beneficial effects of transparency on corruption are contingent on type of transparency, and in particular, who the intended receiver of the information is. Drawing on newly collected data of more than 3.5 million government contracts between 2006 and 2015, the analysis shows that overall tender transparency reduces corruption risks substantially, yet that the effect is largely driven by ex ante transparency, that is, transparency that allows for horizontal monitoring by insiders in the bidding process.